Risk Factors for Noninvasive Ventilation Failure in Children Post-Hematopoietic Cell Transplant - Rowan, Courtney M.; Fitzgerald, Julie C.; Agulnik, Asya; Zinter, Matt S.; Sharron, Matthew P.; Slaven, James E.; Kreml, Erin M.; Bajwa, Rajinder P.S.; Mahadeo, Kris M.; Moffet, Jerelyn; Tarquinio, Keiko M.; Steiner, Marie E. (Frontiers in Oncology, 2021)
Rationale: Little is known on the use of noninvasive ventilation (NIPPV) in pediatric hematopoietic cell transplant (HCT) patients. Objective: We sought to describe the landscape of NIPPV use and to identify risk factors for failure to inform future investigation or quality improvement. Methods: This is a multicenter, retrospective observational cohort of 153 consecutive children post-HCT requiring NIPPV from 2010-2016 Results: 97 (63%) failed NIPPV. Factors associated with failure on univariate analysis included: longer oxygen use prior to NIPPV (p=0.04), vasoactive agent use (p<0.001), and higher respiratory rate at multiple hours of NIPPV use (1hr p=0.02, 2hr p=0.04, 4hr p=0.008, 8hr p=0.002). Using respiratory rate at 4 hours a multivariable model was constructed. This model demonstrated high ability to discriminate NIPPV failure (AUC=0.794) with the following results: respiratory rate >40 at 4 hours [aOR=6.3 9(95% CI: 2.4, 16.4), p<0.001] and vasoactive use [aOR=4.9 (95% CI: 1.9, 13.1), p=0.001]. Of note, 11 patients had a cardiac arrest during intubation (11%) and 3 others arrested prior to intubation. These 14 patients were closer to HCT [14 days (IQR:4, 73) vs 54 (IQR:21,117), p<0.01] and there was a trend toward beginning NIPPV outside of the PICU and arrest during/prior to intubation (p=0.056). Conclusions: In this cohort respiratory rate at 4 hours and vasoactive use are independent risk factors of NIPPV failure. An objective model to predict which children may benefit from a trial of NIPPV, may also inform the timing of both NIPPV initiation and uncomplicated intubation.